Azadirachta indica Attenuates Cisplatin-Induced Nephrotoxicity and Oxidative Stress - Abdel Moneim, Ahmed E. (Hindawi Publishing Corporation, 2014)
We investigated the effects of methanolic leaves extract of Azadirachta indica (MLEN, 500 mg/kg bwt) on cisplatin- (CP-) induced nephrotoxicity and oxidative stress in rats. CP (5 mg/kg bwt) was injected intraperitoneally and MLEN was given by gastric gavage for 5 days before or after CP injection. After 5 days of CP injection, CP-induced injury of the renal tissue was evidenced (i) as histopathological damage of the renal tissue, (ii) as increases in serum uric acid, urea, and creatinine, (iii) as increases in malondialdehyde (MDA) and nitric oxide (NO), (iv) as decreases in the level of glutathione and activities of superoxide dismutase, catalase, glutathione reductase, glutathione-S-transferase, and glutathione peroxidase, and (v) as increase in the expression of nuclear factor kappa B and apoptosis in kidney tissues. However, the oral administration of MLEN to CP-intoxicated rats for 5 days brought back MDA, NO production, and enzymatic and nonenzymatic antioxidants to near normalcy. Moreover, the histological observations evidenced that neem extract effectively rescues the kidney from CP-mediated oxidative damage. Furthermore, PCR results for caspase-3 and caspase-9 and Bax genes showed downregulation in MLEN treated groups. Therefore, Azadirachta indica can be considered a potential candidate for protection of nephrotoxicity induced by cisplatin.